Diskretne strukture - Peterin, Iztok (University of Maribor Press, 2020)
Discrete Structures. This text book brings some branches of Discrete mathematics, which are very applicable in Computer science. As such we start with logic and special emphasis on the proof. The chapter on inductive processes follows. We present the fundamentals of counting and number theory. One part is devoted to recurrence relations, that are a basic tool to describe the processes that are repeating. This enables to quantify the algorithms with respect to the time used by them for their execution. Relations are subsets of the Cartesian product of two sets and present a surprising palette of different results. One direction results in latices and Boolean algebras. We end with graphs. A tool that is incredibly useful mathematical model for all sorts of real life processes.